PENGUKURAN KINERJA ASRI MEDICAL CENTER DALAM PERSPEKTIF BALANCED SCORECARD - Ekorini Listiowati (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
The company performance is a reflection of an activity results and condition of the company. The results of the activities of the company being analyzed, where the results will show the condition of the company's management during the period of performance analysis done. Asri Medical Center (AMC) is one of Muhammadiyah University of Yogyakarta units in health care, education and research belong to da’wa infrastructures. To realize its goal in providing quality health services for people, AMC has to make a performance appraisal regularly and continuously. The objective of this research is to measure the performance of AMC based on the Balanced Scorecard with reference to the performance standards in the AMC. This research is an eksploratoris case study that measured management performance with the Balanced Scorecard, which is assessing the performance not only from the financial aspect but also from non-financial aspects. The subjects of this research are AMC managers, and the data used is the data of 2010 and 2011. The data used are the primary data i.e field studies in the form of interview and observation and also secondary data in the form of general data and specific data on the AMC which includes financial and non financial data. AMC has been running the Balanced Scorecard stages, that is strategy formulation arranged as a result of the macro, industry environments analysis as well as SWOT analysis and has formulated a vision, mission, purpose, basic beliefs, basic values and strategy. The next phase, AMC has developed a strategic plan that includes strategic goal, target and strategic initiatives. The strategic targets have been formulated considering the financial perspective, customer perspective, business process perspective and learning and growth perspective. AMC has to define planning into work program with key performance indicators that can be measured and in accordance with performance standards for each medical center.